История одного города - Салтыков-Щедрин Михаил Евграфович (Классика для школьников, 2021)
Экземпляры: ф. 2 (20211207) / Инвентарный номер: 116088 / Цена: 195.80 / Авт.знак: С 16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1